INVESTIGATING THE EFL UNDERGRADUATE STUDENTS’ PERCEPTION ON THE USE OF SUBTITLE VIDEO FOR VOCABULARY LEARNING - Amalia, Fizi Ashfia (Journal of English Teaching and Learning, 2024)
The integration of technology in vocabulary learning has been well documented in the literature. One of the digital media that is quite widely used by EFL learners is audiovisual media or video more specifically, subtitled videos. Much research has reported the effective use of subtitled videos in learning vocabulary. However, research investigating learners’ perception in learning vocabulary through stubtiled videos is underresearched. To fill this gap, this study aims at finding out the perceptions of EFL undergraduate students towards the use of subtitled videos to learn vocabulary. The research was conducted using a qualitative method with a descriptive approach. 11 EFL undergraduate students voluntarily participated in this study. All data were gathered from group discussions, questionnaires and interviews. The quantitative data were analyzed using descriptive statistics whereas the qualitative data were analyzed thematically. The findings showed that EFL undergraduate students have positive opinions about using videos with subtitles to learn new words. There are 81,8 % students agree and 18,2% students strongly agree with the statement that learning vocabulary through watching video subtitle are interesting also motivating students to learning more. Also, 81,8 % students agree and 18,2% students strongly agree with the statement that watching videos with subtitles students can learn the language authentically.